2016
DOI: 10.1093/hmg/ddw377
|View full text |Cite
|
Sign up to set email alerts
|

Mutation inVPS33Aaffects metabolism of glycosaminoglycans: a new type of mucopolysaccharidosis with severe systemic symptoms

Abstract: Mucopolysaccharidoses (MPS) are a group of genetic deficiencies of lysosomal enzymes that catabolize glycosaminoglycans (GAG). Here we describe a novel MPS-like disease caused by a specific mutation in the VPS33A gene. We identified several Yakut patients showing typical manifestations of MPS: coarse facial features, skeletal abnormalities, hepatosplenomegaly, respiratory problems, mental retardation, and excess secretion of urinary GAG. However, these patients could not be diagnosed enzymatically as MPS. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(104 citation statements)
references
References 36 publications
8
93
0
3
Order By: Relevance
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
“…Mutations in CHEVI or HOPS components commonly cause neurological defects in the C. elegans, D. melanogaster, zebrafish and mice animal models (Fernandes et al, 2014;Harrington et al, 2012;Kim et al, 2004;Peng et al, 2012b;Suzuki et al, 2003;Zhang et al, 2016). Patients carrying mutations in the core components Vps11, Vps16 or Vps33A (Cai et al, 2016;Edvardson et al, 2015;Hörtnagel et al, 2016;Kondo et al, 2017;Zhang et al, 2016) or ARC-causing mutations in the CHEVI subunits also show neurological symptoms (Eastham et al, 2001). Intriguingly, mutations in Vps3 or Vps8 seemingly do not impact neuronal function (Lorincz et al, 2016).…”
Section: Neurological Defectsmentioning
confidence: 99%
“…However, there is evidence of evolutionary divergence within the membrane trafficking system. Metazoan VPS33A and VPS33B are both homologs of the yeast HOPS subunit Vps33 (17), but only VPS33A is found in human HOPS (6,11,18) and mutations in these two homologs generate significantly different phenotypes (19)(20)(21)(22)(23). Also, Vps41 in yeast has been shown to bind directly to Ypt7 (24), but in humans it appears that the analogous interaction (with Rab7) is mediated by an additional protein, RILP (14).…”
Section: Introductionmentioning
confidence: 99%